2001
DOI: 10.1128/jcm.39.9.3260-3266.2001
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Restriction Fragment Length Polymorphisms among Serial Isolates from Patients with Trichophyton rubrum Infection

Abstract: Molecular genotyping of strains of Trichophyton rubrum and T. mentagrophytes from patients with onychomycosis of the toes was performed to ascertain whether the fungal genotype changes over the course of time as sequential samples were obtained from patients receiving antifungal therapy and during follow-up. Sixty-six serial strains of T. rubrum and 11 strains of T. mentagrophytes were obtained from 20 patients (16 patients with T. rubrum, 4 with T. mentagrophytes) who were treated with oral antifungal therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
0
34
0
3
Order By: Relevance
“…The T1 microsatellite developed in our study is the second DNA marker displaying polymorphisms among strains that are otherwise genetically homogenous. Using the TRS marker, a repeat region within the NTS region of the rDNA, several authors were also able to detect variability among isolates of this species (7,6,15). However, no clear association was found with the clinical picture or the geographic origin.…”
Section: Discussionmentioning
confidence: 96%
“…The T1 microsatellite developed in our study is the second DNA marker displaying polymorphisms among strains that are otherwise genetically homogenous. Using the TRS marker, a repeat region within the NTS region of the rDNA, several authors were also able to detect variability among isolates of this species (7,6,15). However, no clear association was found with the clinical picture or the geographic origin.…”
Section: Discussionmentioning
confidence: 96%
“…Given the failure of some of the aforementioned techniques to distinguish T. tonsurans strains (9,10,14,16) and the paucity of sequence information for the species, the rDNA gene locus was selected for this investigation because the flanking 25S, 18S, and 5.8S rDNA sequences are highly conserved among species. In order to unequivocally determine the nature of this locus in T. tonsurans, multiple strains (n ϭ 20), including all those exhibiting length variation in an initial long PCR of the NTS region, were entirely sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations targeting the rRNA locus report the presence of only one strain contributing to infections of the feet and toenails (10,16). In one study, serial isolates were described as switching back and forth between two strain types, but in no sample did the strains occur together (10). In contrast, a single study reported that 60% of onychomycosis specimens were comprised of multiple strains (21).…”
Section: Discussionmentioning
confidence: 95%
“…Yet multistrain infections are infrequently reported in clinical investigations that have evaluated dermatophytes at the molecular level. Several investigations targeting the rRNA locus report the presence of only one strain contributing to infections of the feet and toenails (10,16). In one study, serial isolates were described as switching back and forth between two strain types, but in no sample did the strains occur together (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation